Special paperDouble stent loss during multivessel percutaneous coronary intervention in non-ST-segment elevation acute coronary syndrome - Hawranek, Michał; Desperak, Piotr D.; Gąsior, Paweł M.; Piegza, Jacek; Ciślak, Aneta; Lekston, Andrzej; Gąsior, Mariusz (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
The following description presents a case of a 75-year-old female patient with non-ST-segment elevation acute coronary syndrome in whom there occurred an infrequent complication of percutaneous coronary angioplasty: uncontrolled intracoronary stent displacement from a balloon catheter. During the attempt to retrieve the device using the “small-balloon” technique, further slippage of the stent from the balloon catheter to the right deep femoral artery was observed. Therefore, it was decided to provide a commercial intravascular microloop, whereby the stent was successfully retrieved outside the vascular system.